Pelatihan Dan Belajar Pengolahan Bandeng Cabut Duri Untuk Ibu PKK Dasa Wisma Matahari Di Dusun Gayam, Desa Soko, Kecamatan Glagah. Kabupaten. Lamongan - Aminin; Andi Rahmad Rahim; Nur Maulida Safitri (Universitas Merdeka Surabaya, 2022)
Lamongan is known as a producer of various fishery commodities, both marine fishery and freshwater fishery products. This is directly proportional to the large number of fish farmers scattered in several areas of Lamongan. In Gglagah sub-district itself there are several groups of farmers where the main commodities are fresh vanamei shrimp and milkfish. The problem arose from April to July where there was a big harvest in several areas in East Java, especially Lamongan Regency, so that some fishery commodities such as milkfish, especially in Glagah District, Lamongan Regency experienced a significant decline in prices. One of the efforts to utilize the fish so that it has a high selling value is by processing milkfish into semi-finished products, namely batari (milkfish pull out thorns). The price of unplugged milkfish has a very economical price, in traditional markets with small sizes it can reach Rp. 10,000/head with a net weight of 130-180 grams, while large sizes with a net weight of 330-380 grams can reach a price of Rp. 20,000/head. Planned Location for the implementation of internal community service at the University of Muhammadiyah Gresik is in Guayam Hamlet, Soko Village, Glagah District, Lamongan Regency, a village where the majority of the population are pond farmers, approximately 75% of pond farmers and 25% are factory workers. The purpose of implementing the internal community service activities at the University of Muhammadiyah Gresik is to first open up business opportunities and job opportunities. The second is to cultivate an entrepreneurial spirit in the community and the third is to produce processed products of Milkfish Cabut Duri. The methods used are lecture and discussion methods, knowledge transfer and demonstration methods. Through guidance in UMG's internal community service program, it is hoped that PKK can utilize all parts of milkfish whose selling price is low from April to July into processed products with high economic value. so that farmers and villagers will benefit